Пояса безопасности угольных шахт Донбасса - Коболев, В. П. (Национальный технический университет "Харьковский политехнический институт", 2019)
Цель. Рассмотрение природы катастрофических событий на шахтах Донецкого угольного бассейна. Методика. Структурно–тектонический анализ упруго–напряженного состояния Складчатого Донбасса. Результаты. В статье обсуждаются вопросы геологического строения и физического состояния Складчатого Донбасса, как основы для оптимальной раскройки шахтных полей, безопасности горных работ, эффективной добычи угля и сопутствующего газа–метана. Практическая значимость. Предложены методы возможного устранения внезапных выбросов угля, породы и газа в форме лавинообразного разрушения призабойной части угольного (породного) массива и практические пути повышения безопасности горных работ. Научная новизна. Способы разгрузки массива вокруг горных выработок, с учетом упруго–напряженного состояния Донбасса и параметров путей миграции горючих газов.

Purpose. Consideration of the nature of the occurrence of catastrophic events in the mines of the Donetsk coal basin. Methods. Geological Structural and tectonic analysis of the elastic–stressed state of the Folded Donbass. Findings. The article discusses issues of the geological structure and physical condition of the Folded Donbass, as the basis for the optimal cutting of mine fields, mining safety, efficient mining of coal and associated methane gas. Originality. Methods of unloading the array around the mine workings, taking into account the elastic–stress state of the Donbass and the parameters of the migration routes of combustible gases. Practical implications. Methods are proposed for the possible elimination of sudden emissions of coal, rock and gas in the form of an avalanche–like destruction of the bottom–hole part of the coal (rock) massif and practical ways to improve the safety of mining operations.
Safety belts of the donets basin coal mine
Keywords: складчатый Донбасс; структурно–тектонический анализ; катастрофические события; folded Donbass; structural and tectonic analysis; catastrophic events